2021
DOI: 10.1111/aji.13483
|View full text |Cite
|
Sign up to set email alerts
|

Increased cell‐free fetal DNA release after apoptosis and sterile inflammation in human trophoblast cells

Abstract: Problem Cell‐free fetal DNA (cffDNA) shed from the placenta can be detected in maternal blood and increases incrementally during gestation. Concentrations are further elevated with pregnancy complications. Specific activators of cffDNA release in such complications have not been identified. Here, we use trophoblast cells from early and term placenta to examine cffDNA release following apoptosis, infection, and sterile inflammatory stress. Method of Study HTR8/SVneo cells were used to model first‐trimester trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It is known that cffDNA can stimulate inflammation in several tissues and cell types ( Goldfarb et al, 2018 ; Kazemi et al, 2021 ; Yeganeh Kazemi et al, 2021 ) but its effects have not yet been studied on the human FM. In addition to this, it is also known that the sex of the fetus can influence both the magnitude and the resultant cytokine profile of the inflammatory response, depending on the specific circumstances ( Burns et al, 2015 ; Mitchell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that cffDNA can stimulate inflammation in several tissues and cell types ( Goldfarb et al, 2018 ; Kazemi et al, 2021 ; Yeganeh Kazemi et al, 2021 ) but its effects have not yet been studied on the human FM. In addition to this, it is also known that the sex of the fetus can influence both the magnitude and the resultant cytokine profile of the inflammatory response, depending on the specific circumstances ( Burns et al, 2015 ; Mitchell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased circulating levels of cffDNA have also been associated with adverse pregnancy outcomes and pathologies such as; preeclampsia (Martin et al, 2014;Kwak et al, 2020), gestational diabetes (Hopkins et al, 2020), and preterm birth (Gomez-Lopez et al, 2020). cffDNA from the trophoblast is also known to increase by sterile inflammation, via HMGB1 (Yaganeh Kazemi et al, 2021), but its ability to generate inflammation itself is contentious. Some studies have clearly shown that it is able to interact with toll-like receptor 9 (TLR9) (Goldfarb et al, 2018) and that immune cells respond to it by producing inflammatory cytokines (Yeganeh Kazemi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liberation of cffDNA can be affected by doxorubicin and high-mobility group box protein-1, which are inflammatory agents. Conversely, lipopolysaccharide does not affect the release of early or term cffDNA [16] , suggesting that cffDNA is involved in sterile inflammation as opposed to infectious processes. Sterile inflammation may lead to placental dysfunction and consequently cause pregnancy complications.…”
Section: Discussionmentioning
confidence: 88%